Parent's knowledge and attitude towards their children's oral health and timing of the first dental visit in AL-Madinah city - Mohammed I. Al-Zahrani (Elsevier, 2019)
Introduction: Dental caries remains the most common disease affecting humans. Numerous studies have reviewed the effectiveness of different preventive measures in different populations. Parents are decision-makers of children health and healthcare, thus they play an important role in achieving the best oral health outcomes of their young children. Considering parent's important role in the well being of young children, it is essential to explore their knowledge, attitude and believes as it affects the dental care. Aims of the study: (1) To assess knowledge and attitude of parents regarding their children oral health. (2) To assess knowledge and attitude of parents regarding the timing of first dental visit of their children. Subjects and methods: The study population was consisted of the parents attending the Dental Center, King Fahd Hospital, AL-Madinah, Saudi Arabia. A self-administered questionnaire, with cover page included for the invitation of the parents to participate in the study, electiveness of participation and explanation of the study purpose, was completed by the parents to assess their knowledge regarding oral health and timing of the first dental visit of their children. Results: Three hundred and fifty questionnaires were distributed to the visiting parents at Dental Center and three hundred nine questioners had been returned for statistical analysis using a statistical package for social sciences (SPSS). The response rate was found to be 88.3%.